Stock return reaction to unusual market activity announcement : evidence from the ace market in Malaysia - Chen, Siong Yain (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study examines the effect of Unusual Market Activity (UMA) announcement on stock return in Malaysian market with a sample of 62 companies listed on the ACE market Bursa Malaysia for the period of 2007-2015. This study employs event study methodology. More specifically, it employs the market model in generating abnormal returns surrounding subsequent UMA announcements. t-test is applied to evaluate the abnormal return from the market model. The findings show that there are few days in which the average abnormal return (AAR) and cumulative average abnormal return (CAAR) are statistically significant. In addition, this study also further investigates the abnormal return (AR) and cumulative abnormal return (CAR) for individual companies. It is found that majority of the stocks returns fell significantly 30 days after the UMA announcement. The magnitude of fall in returns ranges from 4% to 234%. Hence, it is not advisable for investors to buy stock after UMA announcement.